BAGAIMANAKAH HUKUM ADAT MENYELESAIKAN KASUS PENGANIAYAAN? (Studi Pada Masyarakat Adat Petalangan di Kecamatan Bandar Petalangan Kabupaten Pelalawan Provinsi Riau) - Bela Islami; Evi Deliana; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Arrangements regarding the crime of persecution are regulated in article 351of the Criminal Code. In Indonesia's positive law it is clear that if a person commitsan intentional act aimed at damaging the health of another person, he will be subjectto a prison sentence of 2 years and 8 months as stipulated in article 351 of theCriminal Code. But the settlement of the crime of persecution through the Petalangancustomary law is not the case. If the case of the crime of persecution is resolvedthrough the Petalangan customary law, it will be resolved peacefully throughdeliberation and bringing together the perpetrators and victims and improving orderin society.From the results of research and discussion, there are several points that canbe concluded. First, in the community in Bandar Petalangan subdistrict, cases ofcriminal acts of persecution were mostly resolved through Petalangan customary law.Second, the settlement through the Petalangan Customary Law fulfills the wishes ofthe people because it also improves the order to the previous situation. Third, thatthe resolution of the criminal act of persecution through the Petalangan CustomaryLaw does not have an element of revenge, rather it is about reconciling theperpetrator and the victim. The author's suggestion is that it is necessary to digdeeper and spread understanding about Petalangan Customary Law, so that theinjunctions about Customary Law, especially regarding criminal acts, continue to bepreserved by the community.Keywords: Settlement-Persecution-Customary Law